Float Glass Innovation in the Flat Glass Industry - Uusitalo, Olavi (SpringerBriefs in Applied Sciences and Technology, 2014)
A thorough industry analysis is of utmost importance for a study on the impact of technological changes on industry structure. This book evaluates the consequences of a vaguely chosen level of an industry analysis. Too broad a definition of the industry may disaggregate sub-industries, processing industries and international aspects. This is illustrated by revisiting an industry study upon which the dominant design model was based. Readers will see and understand the consequences of too broadly defined industries together with quantitative research approach can have. The book argues that the nature of the industry should define the level of the analysis. This is done by revisiting the flat glass industry study, on which Anderson and Tushman's (1990) dominant design model is partly based. In their study Anderson and Tushman defined the flat glass industry based on four-digit SIC codes. It is argued that this definition was too broad and it disaggregated important sub-industries, processing industries and international aspects. This study uses more accurate analysis in five-digit SIC codes. The empirical findings of this study and Anderson and Tushman's study are different. Their broader industry definition revealed only the flat glass industry not two sub-industries: plate glass and sheet glass. According to this study the nature of the industry should define the level of the analysis and performance parameter should defined be based on effectiveness instead of efficiency of the innovation. As a consequence of these clarifications this study regards contrary to Anderson and Tushman float glass as the dominant design.